2018
DOI: 10.1111/imb.12494
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of doublesex in Bemisia tabaci

Abstract: Bemisia tabaci (Gennadius) is an important agricultural pest with a worldwide distribution. Although B. tabaci is known to have a unique haplodiploid reproductive strategy, its sex determination mechanism is largely unknown. In this study, we cloned the full-length sequence of B. tabaci doublesex (Btdsx) and found that Btdsx has 28 splicing isoforms. We found two new splicing isoforms of transformer 2 (Bttra2), which encode two proteins. We also confirmed that both genes lack sex-specific splicing isoforms. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 75 publications
2
44
0
Order By: Relevance
“…In P. humanus (Phthiraptera), the alternative splicing of dsx follows the usual pattern, with a common N-terminal domain and alternative C-termini, but we found that both dsx isoforms are present in both sexes. Previous work in the hemipteran Bemisia tabaci also failed to detect sex-specific dsx isoforms (95), suggesting that some insects may have secondarily lost sex-specific dsx splicing.…”
Section: Discussionmentioning
confidence: 95%
“…In P. humanus (Phthiraptera), the alternative splicing of dsx follows the usual pattern, with a common N-terminal domain and alternative C-termini, but we found that both dsx isoforms are present in both sexes. Previous work in the hemipteran Bemisia tabaci also failed to detect sex-specific dsx isoforms (95), suggesting that some insects may have secondarily lost sex-specific dsx splicing.…”
Section: Discussionmentioning
confidence: 95%
“…S2; Table ). Among these genes, PSI , tra2 and dsx have been documented previously (Xie et al ., ; Liu et al ., ; Guo et al ., ), whereas the other 23 (88.5%), including tra and fru , were identified for the first time in this study.…”
Section: Resultsmentioning
confidence: 63%
“…Second, 20 SDGs with incomplete sequences or the same predicted amino acids between the female and male transcriptomic datasets were filtered (Table S5). The remaining six SDGs were verified by RT‐PCR [ dsx , tra2 and PSI verified previously (Liu et al ., ; Guo et al ., ) and da , mle and Imp verified in this paper]. PCR validation in this paper was conducted using designed sex‐specific primers (Table S7) with newly emerged female or male samples.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations